Дипломатическата кариера на Константин Петкович - Никодимова, Галина (Slavica Lodziensia, 2019)
The paper presents one of the many dimensions of Konstantin Petkovic’s case – his diplomatic career in the service of the Russian Empire. Konstantin Petkovic is a part of the team of the leading Russian diplomat – Alexander Mikhailovich Gorchakov. He is the last chancellor of the Russian Empire and head of the foreign policy of the Northern Empire during the reign of Emperor Alexander II. His diplomatic career is in Ragusa (Dubrovnik) and Lebanon.